Metabolomics Study on the Resistance of Walnut Peel to Colletotrichum gloeosporioides under Prochloraz Treatment. (28th June 2022) - Yang, Xia; Wu, Liuyan; Fu, Li; Fu, Pin; Zhu, Jiamin; Zhao, Yuxue; Liu, Jing
Abstract : Anthracnose, caused by Colletotrichum gloeosporioides, is highly harmful for walnut production in the world. To better control this disease, the inhibitory effects of 3 fungicides against Colletotrichum gloeosporioides were determined, and the results showed that prochloraz had better inhibitory activity. Through comparative metabolomics analysis, 311 metabolites might be associated with the walnut peel response to Colletotrichum gloeosporioides under prochloraz treatment. Furthermore, we supposed that the phenylpropanoid pathway might be induced by prochloraz to resist Colletotrichum gloeosporioides infection. In conclusion, the upregulated metabolites in the phenylpropanoid pathway might be related to synthesize lignin to further form a cell wall against Colletotrichum gloeosporioides infection.